An evaluation of the palliative care unit at Groote Schuur Hospital - Robertson, Cara (Department of Public Health and Family Medicine, 2015)
Background: Patients often present to the Emergency Department (ED) at the end of life. Caring for these patients present a unique set of challenges, and often the patients' and families' needs are at odds with the pervasive rescue-oriented ED culture. A potential solution to this problem is an Acute Palliative Care Unit. Groote Schuur Hospital opened such a unit in April 2011, managed by the ED staff. This kind of service was not available in this tertiary, academic state hospital prior to that. Objectives: This study aimed to evaluate aspects of care at the Groote Schuur Hospital Palliative Care unit by designing a questionnaire based on the Liverpool Care Pathway assessing elements of care, describing the population admitted demographically, recording outcomes and making recommendations based on the findings. Methods: A retrospective folder review was completed on all patients who were admitted to the unit between April 2011 and May 2013. Data was collected onto an Excel spreadsheet, and was analysed using the SmallStata 13 software package. Demographic data collected included sex, age, area from which the referral came, diagnosis, length of stay and outcomes. Data on care were grouped into physical care, psychological care, spiritual care, communication skills and bereavement care. Results: 176 folders were identified. 167 were reviewed (nine were missing). Nine folders did not meet inclusion criteria. 158 folders were included in the study. The vast majority of patients were admitted from home via the ED. Mean age was 59.49 years (95% CI 56.76 – 61.53). Median length of stay was 25 hours (IQR 7-47). 97 patients had palliative care needs in the absence of malignancy, 60 had cancer. 111 (70.7%) patients died in the unit, 5 (3.18%) died en route to the unit, 16 (10.19%) went home, 8 (5. 1%) were referred back to other specialities and 17 (10.83%) were referred to step down facilities. 96% of patients had their medication adjusted, and 128 (81.53%) were commenced on syringe drivers. Morphine, haloperidol and hyoscine butyl bromide were the commonest prescribed medicine in the syringe driver. None of the patients had an official "Do Not Resuscitate" (DNR) form completed, but more than 75% of patients had a note or clear proxy measures indicating that resuscitation is not indicated. Difficulty with communication was present in 8 (5.26%) patients and 10 (6.58%) families. Less than 15% of patients had documented psychological support and less than 30% had documented spiritual care. Bereavement care was also poorly documented. Conclusion: This study described the demographics of, and evaluated the care offered in the Groote Schuur End-of-Life unit. Much of the care is comparable to current recommendations, but there is concern that symptoms may be underestimated in the absence of formal tools. Recommendations include using different terminology w.r.t. the unit, establishing a consulting and outpatient service based at the hospital, implementing formal symptom assessment tools, implementing the formal policy w.r.t. DNR orders, and improved overall documentation. There is scope for further research on interventions such as this one, especially on its impact on staff and its cost-effectiveness. This model of care achieves care comparable to current global recommendations in end-of-life care and can be implemented in similarly resource-restricted contexts.